2016
DOI: 10.1074/jbc.m116.737577
|View full text |Cite
|
Sign up to set email alerts
|

Family-specific Kinesin Structures Reveal Neck-linker Length Based on Initiation of the Coiled-coil

Abstract: and -7 generate processive hand-over-hand 8-nm steps to transport intracellular cargoes toward the microtubule plus end. This processive motility requires gating mechanisms to coordinate the mechanochemical cycles of the two motor heads to sustain the processive run. A key structural element believed to regulate the degree of processivity is the necklinker, a short peptide of 12-18 residues, which connects the motor domain to its coiled-coil stalk. Although a shorter necklinker has been correlated with longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Moreover, this study reinforced the importance of conjoining the native sequences of both the native neck linker and helix a7 for engineered constructs to study the motile properties of kinesin family members (80). In addition, the Phillips et al structural study revealed similar disparities in the coiled-coil predictions for a wide variety of non-motor proteins in the Protein Data Bank (80).…”
Section: Structural Studies Show That the Coiled-coil Predictions Wermentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, this study reinforced the importance of conjoining the native sequences of both the native neck linker and helix a7 for engineered constructs to study the motile properties of kinesin family members (80). In addition, the Phillips et al structural study revealed similar disparities in the coiled-coil predictions for a wide variety of non-motor proteins in the Protein Data Bank (80).…”
Section: Structural Studies Show That the Coiled-coil Predictions Wermentioning
confidence: 77%
“…Therefore, the neck linker is shortened from 17 residues to 12 residues, thus shorter than the neck linker of kinesin-1 at 14 residues. The crystal structures of both Eg5 and CENP-E reveal much shorter neck linkers than predicted (80). Helix a7 of Eg5 begins at Lys-371 instead of Ile-375, thus shortening the neck linker from the predicted 18 residues to 14 residues.…”
Section: Structural Studies Show That the Coiled-coil Predictions Wermentioning
confidence: 99%
“…( C ) The three‐dimensional structure of hCENP‐E's Neck‐linker and alpha 7 helix (PDB No. 5JVP) [Phillips et al., ]. ( D ) The molecular kinetics of CENP‐E on microtubules.…”
Section: The Structural Domains and Functional Motifs Of Kinesin‐7 Cementioning
confidence: 99%
“…Additional evidence in support of this hypothesis is that the sequence of the neck linker followed by helix ␣7 for KIF3B and KIF3C are identical with the exception of a single residue. Furthermore, the structures of the neck linkers and ␣7 for KIF3A and KIF3C, and hence KIF3B, are very similar (71). Thus, it is likely that the modulation arises from interactions between the motor domains themselves that cannot be achieved by the homodimers despite how catalytically similar KIF3AA and KIF3BB are.…”
Section: Discussionmentioning
confidence: 95%